Enhancing barley resilience to thermo-hydric stress through conservation agriculture in semi-arid western Tunisia - Somrani, Olfa; Oueslati, Oussama; Bchini, Houcine; Rezgui, Mounir; Marzougui, Salem; Bahri, Haithem; Annabi, Mohamed; Rezgui, Mohsen (Journal of Agriculture and Natural Resources, 2025)
This study aimed to evaluate the resilience of two barley varieties (‘Ardhaoui’ and ‘Manel’) to thermo-hydric stress under conservation agriculture (CA) compared to conventional agriculture, across different sowing dates (normal, late) and water regimes (rainfed, irrigated). Field experiments were conducted during the 2020–2021 winter growing season at a representative semi-arid site in Western Tunisia, and climatic trends over the past 24 years were analyzed to contextualize current stress conditions. A severe water deficit, coupled with a rise in temperature and increased ET0, occurred during grain filling. This tendency towards climate change is confirmed by the site's climatic characterization over 24 years, during which temperatures have risen by 0.16 °C per year (r = 0.800, p = 0.01). Results showed that CA significantly improved barley performance, increasing biological and grain yields by 26% and 29%, respectively, suggesting more efficient rainfall utilization. Supplemental irrigation further enhanced grain yield (51%) relative to biological yield (45%). The local variety ‘Ardhaoui’ demonstrated higher tolerance to drought and heat stress than the improved variety ‘Manel’. Biomass was more sensitive to heat stress than grain yield (32% vs. 24%), indicating a potential shift in harvest index under extreme conditions. Stress tolerance indices (HSTI and STI) and phenolic compound analysis confirmed that CA and supplemental irrigation mitigated the negative effects of thermo-hydric stress. The significant positive interaction (p = 0.001) between tillage method and sowing date confirms that tillage practices alleviate heat stress expression. These findings highlight that CA, when combined with appropriate variety selection and irrigation management, can improve barley resilience under semi-arid conditions. The study also underscores the importance of local varieties in adapting to climate variability, while cautioning that results are based on a single season and site, and multi-year evaluations are needed to confirm long-term benefits.